2021
DOI: 10.1007/s10663-021-09517-6
|View full text |Cite
|
Sign up to set email alerts
|

Policy instruments and self-reported impacts of the adoption of energy saving technologies in the DACH region

Abstract: Using a large sample of enterprises from a survey that was simultaneously conducted in Germany, Austria and Switzerland, we study the self-reported impacts of the adoption of “green” energy saving and related technologies (GETs). Our specific interest is in how different policy instruments associate with energy efficiency, the reduction of $$\hbox {CO}_{2}$$ CO 2 emissions, and competitiveness at the firm level. A first set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…Moreover, our findings are in line with previous investigations showing that economic and relative advantages are the most important factors influencing the decisions to adopt energy-saving technologies. This research also replenishes previous studies about organizational adoption of technologies, e.g., [17,20,26], and about adopting energy-saving technologies [2,[5][6][7], by showing the influence of legal obligations on adopting energysaving technology behavior. Previous studies find regulatory and normative pressures as conditions under which firms pursue environmental innovations, see, e.g., [20,26], the means to stimulate awareness to preserve energy, and incentives to reduce implementational costs of energy-saving technologies [5], subsidies that stimulate investments in energy efficiency [2], a mix of subsidies, taxes, and standards that are perceived to influence energy-saving investment decisions [6], and taxes/quotas in relation to early adoption of energy-saving technologies [7].…”
Section: Theoretical Implicationssupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, our findings are in line with previous investigations showing that economic and relative advantages are the most important factors influencing the decisions to adopt energy-saving technologies. This research also replenishes previous studies about organizational adoption of technologies, e.g., [17,20,26], and about adopting energy-saving technologies [2,[5][6][7], by showing the influence of legal obligations on adopting energysaving technology behavior. Previous studies find regulatory and normative pressures as conditions under which firms pursue environmental innovations, see, e.g., [20,26], the means to stimulate awareness to preserve energy, and incentives to reduce implementational costs of energy-saving technologies [5], subsidies that stimulate investments in energy efficiency [2], a mix of subsidies, taxes, and standards that are perceived to influence energy-saving investment decisions [6], and taxes/quotas in relation to early adoption of energy-saving technologies [7].…”
Section: Theoretical Implicationssupporting
confidence: 68%
“…Though many organizations have adopted technologies imposed by governmental laws, up until now, there has been a lot of energy-saving potential-unused for service and industrial organizations [4]; moreover, differences in the adoption of energy-saving technologies (between countries and sectors) are large [5]. Researchers have investigated the factors influencing the adoption of energy-saving technologies, including the environmental policies of taxation, subsidies, standards, quotas and the ETS-system [2,[5][6][7], economic and environmental considerations, e.g., [8,9], social and personal considerations, e.g., [10], and firm and technology characteristics, e.g., [11,12]. See Fu, Kok [13] for a broad overview of factors influencing the adoption of sustainable process technologies, including energysaving technologies, based on a systematic literature review.…”
Section: Introductionmentioning
confidence: 99%
“…However, green innovation was also found to have no connection with EU-ETS (Lofgren et al 2014 ). In the case of the CN-ETS, authors also found similar inconclusive findings, for instance, positive (Ning et al 2022 ; Zhu et al 2019a ), negative (Chen et al 2022 ; Zhang et al 2019b ), mixed or inverted-U and U-shaped (Peneder et al 2022 ; Song et al 2020 ; Zhang et al 2022a ; Zhuge et al 2020 ), no effect or not significant (Shen et al 2020b ; Wu and Lin 2022 ). Thus, the impact of ETSs on green innovation remains inconclusive and varies in terms of geographical and sectoral heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 81%
“…ER negatively affects the FGI efficiency in the short run (Tang et al 2020b ). Recently, a few studies also attempted to investigate the embedding effects of CN-ETS on enterprises’ GI and found no significant effect (Peneder et al 2022 ; Shen et al 2020a ; Tang et al 2021 ; Xing et al 2019 ). Another recent study found a significant negative relationship between CN-ETS and green innovation (Chen et al 2021 ).…”
Section: Possible Reasons For Detrimental Effectsmentioning
confidence: 99%
“…In the fourth paper of this special issue, Peneder et al ( 2021 ) study the adoption of “green energy saving and related technologies” (GETs) based on a survey among companies in the DACH region (Germany, Austria and Switzerland). On the one hand, the authors investigate the main determinants of the adoption of GETs in different areas (e.g.…”
mentioning
confidence: 99%